GENERAL EDUCATION IN INDONESIAN GENERAL COMPULSORY COURSES OF LANGUAGES OF SYIAH KUALA UNIVERSITY STRENGTHENS STUDENT IDENTITY - S Subhayni (Geuthèë Institute, Aceh, 2018)
General Education is very important to be implemented by universities and the stakeholders to become a foundation in the implementation of character education in universities. The growth and development of good character and values will encourage students to grow with capacity and commitment to do the best things and do everything right, clear, and purposeful life goals. This study aims to describe general education in Indonesian General Compulsory Courses of Languages at Syiah Kuala University to strengthen student identity. This research is descriptive with a qualitative approach with a sample of 40 students. Research data was collected through observation. The results of the study indicate that the value of student character is good and there are efforts in students to strengthen their identity. Thus, in generally of FKIP Unsyiah students who are taking Indonesian General Compulsory Courses of Languageshave applied character values in their daily lives well, although there are still some student characters that still need to be improved